2009
DOI: 10.3945/jn.109.106765
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin Dimers A1, A2, and B2 Are Absorbed without Conjugation or Methylation from the Small Intestine of Rats

Abstract: Intervention studies with procyanidin (PC)-rich extracts and products such as cocoa and wine suggest protective effects of PC against cardiovascular diseases. However, there is no consensus on the absorption and metabolism of PC dimers. Interestingly, nothing is known about the absorption of A-type PC. In this study, the absorption and metabolism of purified PC dimers A1 [epicatechin-(2-O-7, 4-8)-catechin], A2 [epicatechin-(2-O-7, 4-8)-epicatechin], and B2 [epicatechin-(4-8)-epicatechin], A-type trimers, a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
130
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(143 citation statements)
references
References 25 publications
12
130
1
Order By: Relevance
“…Since only flavonol monomers and dimeric proanthocyanidins are absorbed [58][59][60][61], systemic effects of proanthocyanidins would be limited to these compounds or eventually to not yet characterized metabolites and/or colonic degradation products from the polymeric molecules [58]. In this context, our findings cannot help to rationalize the cardiovascular protection nor provide a molecular interpretation for the anti-inflammatory effects of pistachio nut diets [20].…”
Section: Conclusive Remarksmentioning
confidence: 89%
“…Since only flavonol monomers and dimeric proanthocyanidins are absorbed [58][59][60][61], systemic effects of proanthocyanidins would be limited to these compounds or eventually to not yet characterized metabolites and/or colonic degradation products from the polymeric molecules [58]. In this context, our findings cannot help to rationalize the cardiovascular protection nor provide a molecular interpretation for the anti-inflammatory effects of pistachio nut diets [20].…”
Section: Conclusive Remarksmentioning
confidence: 89%
“…To understand the beneficial biological activities of catechins, a tremendous amount of research has examined the absorption and metabolism of catechins, and deconjugation enzymes are often used in the experiments. [18][19][20] However, there is no report demonstrating that catechins were present in the deconjugation enzymes. This may be because in those studies, they dealt with the application C 3 10 5 10 EC 3 10 5 10 GC 3 10 5 10 EGC 3 10 5 10 Cg 3 10 2 5 ECg 3 10 2 5 GCg 3 10 5 10 EGCg 3 10 5 10 The detection limit was a signal-to-noise ratio of more than 3:1, and the quantification limit was a signal-to-noise ratio of more than 10:1.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus likely that high-molecular-weight and low-molecular-weight polyphenols inhibit cell degranulation by different mechanisms. Since it has been reported that only low-molecular-weight polyphenols, epicatechin, procyanidin A1, A2, and B2, can be absorbed in the digestive tract, 22) and only partially, our study focused on the PSEL fraction to clarify its inhibitory mechanism against degranulation.…”
Section: Resultsmentioning
confidence: 99%